Influence of different parameters on the decrease of extra-activity studies myocardial Gated-SPECT - Rodrigues, Andreia (2013)
Introduction – Myocardial perfusion imaging (MPI) is one of the most indicated complementary diagnostic exams in cardiovascular disease. Extra myocardial activity is a recurrent problem in the acquisition and evaluation of functional images. Parameters like the radiotracer (RT), the stress protocol, the ingestion of different aliments; the positioning, and imaging processing interfere with extra-myocardial activity in MPI. The aim of this study is to identify the protocol of MPI at the national level and assess the percentage of repetitions of acquisitions caused by this problem. Methodology – For this study, the population selected was the Nuclear Medicine Services (NMS) in Continental Portugal. Were analyzed 15 surveys answered by the Technical Coordinators of the various NMS. The association of behavior of the variables has been made using descriptive statistics and the Spearman Correlation Coefficient. Results – The percentage of repetitions decrease with 99mTechnetium (Tc)-Tetrofosmine, delayed imaging, eating (water, milk, juice, bread with butter), and with attenuation correction. Conclusion – The results achieved in this study demonstrate that the majority of solutions in NMS produce a decrease in exam repetitions.